2015
DOI: 10.1111/1471-0528.13280
|View full text |Cite
|
Sign up to set email alerts
|

Vegan-vegetarian diets in pregnancy: danger or panacea? A systematic narrative review

Abstract: Background Although vegan-vegetarian diets are increasingly popular, no recent systematic reviews on vegan-vegetarian diets in pregnancy exist.Objectives To review the literature on vegan-vegetarian diets and pregnancy outcomes.Search strategy PubMed, Embase, and the Cochrane library were searched from inception to September 2013 for pregnancy and vegan or vegetarian Medical Subject Headings (MeSH) and freetext terms.Selection criteria Vegan or vegetarian diets in healthy pregnant women. We excluded case repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 62 publications
0
73
1
13
Order By: Relevance
“…The inclusion of milk and eggs is associated with the adequate supply of nutrients to pregnant women, while the exclusion of all animal foods makes the vegan diet likely inadequate in this life period, if not properly integrated. A systematic review of the literature highlighted an increased risk of iron and vitamin B 12 deficiency and low birth weight in association with vegetarian or strictly vegan diets, despite the absence of adverse effects for the fetus [79]. …”
Section: Focus On Conditions Associated With Nutrient Deficienciesmentioning
confidence: 99%
“…The inclusion of milk and eggs is associated with the adequate supply of nutrients to pregnant women, while the exclusion of all animal foods makes the vegan diet likely inadequate in this life period, if not properly integrated. A systematic review of the literature highlighted an increased risk of iron and vitamin B 12 deficiency and low birth weight in association with vegetarian or strictly vegan diets, despite the absence of adverse effects for the fetus [79]. …”
Section: Focus On Conditions Associated With Nutrient Deficienciesmentioning
confidence: 99%
“…Some studies have found that some vegans had inadequate intakes of B12, where particular concerns have been raised over the B12 status of older people due to their limited absorption capacity and of pregnant women due to their higher demands (Majchrzak et al 2006;Waldmann et al 2005;Donaldson 2000;ADA 2009;Piccoli et al 2015). This is not a reason to eat flesh, as B12 binds with the protein in animal foods, impeding absorption, which is precisely why older people are better off with vegan sources of B12 (Norris and Messina 2011, 31).…”
Section: Vitamin B12mentioning
confidence: 99%
“…A low intake of saturated fats and large amounts of vegetables, fruits, whole grains, legumes, soy products, nuts and seeds are characteristic of vegetarian and vegan diets, causing lower cholesterol levels and better control of blood glucose. The Academy of Nutrition and Dietetics [27] notes that vegans need reliable sources of vitamin B12 from fortified foods or supplements, as confirmed by the study by Piccoli et al [28], suggesting nutritional deficiencies in pregnant women, mainly in iron, vitamin B12 and D and calcium intake. That is why it is important to present as reliable as possible knowledge and to continue improving people's state of consciousness of in both the positive and negative health effects of vegetarian diets [26].…”
Section: Discussionmentioning
confidence: 90%